Teaching and Learning for Education in 21st Century: Skill Development and Students’ Learning Outcome in Biology in Oyo State: Skill Development and Students’ Learning Outcome in Biology in Oyo State - Amoo, Olufunmilayo (African Journal of Behavioural and Scale Development Research, 2023)
Abstract Biology being one of the important science subject to science learners intending to do programmes such as medicine, nursing, physiotherapy, anatomy, physiology, animal production and health among others and also a subject that entails theory and practical. There is need for such learners to develop skills in relation to content which may bring about improvement in learning. Therefore, a direct instruction and collaborative learning were used. A pretest -posttest-approach was used in a quasi-experimental design. Ibadan is divided into four educational zones in which one was chosen by random sampling and purpose sampling was used in and purposive sampling was used in selecting four schools and from each school, an arm of SS2 science intact class was used totaling 135 learners. Three instruments were used: Achievement Biology Test (ABT) (r = .78), direct instruction guide (DIG) and collaborative learning guide (CLG). Two hypotheses were evaluated at p = 0.05. Data analysis used were mean, standard deviation and analysis of covariance. The result revealed that there was a significant effect of collaborative learning on pre -test and posttest of learners’ academic achievement with high mean score ( while in direct instruction there was no significant effect of direct instruction on pretest and posttest of learners’ academic achievement with low mean score ( . The outcome showed a considerable impact of the treatments (collaborative learning and direct instruction) on learners’ academic achievement [F (2, 135) = 291.476, p=.000]. Additionally, it was shown that there is no significant effects of learners’ gender on academic achievements of direct instruction and collaborative learning achievement [F (2, 135) = 1.491, p=.224]. It was recommended collaborative learning should be encouraged and adopted during teaching/learning of Biology.